A Review on Ultrafast Laser Microwelding of Transparent Materials and Transparent Material–Metals - Jiayi Xu; Qing Jiang; Jin Yang; Jiangmei Cui; Yixuan Zhao; Min Zheng; J. P. Oliveira; Zhi Zeng; Rui Pan; Shujun Chen (Metals, 2023)
Transparent hard and brittle (THB) materials have generated significant interest due to their excellent properties, such as wide spectral transmittance, heat resistance, chemical inactivity and high mechanical strength. To further explore the application of THB materials, it is inevitable to be confronted with a range of joining THB materials and THB material–metals. Ultrafast (UF) laser microwelding enables a new means of joining THB materials and THB material–metals, due to a localized energy deposition method, which is dominated by nonlinear absorption. This process can realize high-quality micro-zone direct joining of THB materials or THB material–metals without the assistance of a light-absorbing intermediate layer. In this paper, we review the advances in UF laser microwelding of THB materials and THB material–metals considering the last two decades, from the analysis of the interaction mechanism between UF laser and matter to the key influencing factors and practical applications of this technology. Finally, the existing problems and the future research focus of UF laser microwelding technology of THB materials and THB material–metals are discussed.